Figurative Languages Employed by EFL Lecturers in Teaching - Fatimah Fatimah; Siti Hardiyanti Amri; Rusan Rusan (JELITA, 2020)
The objectives of this study are to find out (1) kinds of figurative languages used by EFL lecturers (2) reasons for using figurative languages in teaching, and (3) students’ responses on the use of figurative languages by EFL lecturers in teaching. The current research employed the descriptive qualitative method. The subjects of this research are two EFL lecturers and students at English Education Study Program of STKIP Dampal Selatan. The results of the research indicated that (1) kinds of figurative languages employed by EFL lecturers in teaching are: rhetoric, simile, metonymy, personification, repetition, paradox, metaphor, and litotes, (2) the reasons for using figurative languages are: to help students’ understanding the lessons, in motivating students in learning process, for introducing language and culture, as a feedback to increase students’ understanding on the lessons, and to train students’ critical thinking. In addition, (3) the students’ responses on the use of figurative language is the students easily in association the material with the real world absorbed because those make closer with their environment; those also could enrich their knowledge on languages; and figurative languages used by lecturers help them to understand the lesson.